2017
DOI: 10.2147/ijn.s141549
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects on myocardial infarction model: delivery of schisandrin B using matrix metalloproteinase-sensitive peptide-modified, PEGylated lipid nanoparticles

Abstract: Purpose Schisandrin B (Sch B) is clinically applied for the treatment of hepatitis and ischemic disease. However, its clinical efficacy is limited due to the poor solubility and low bioavailability. This study aimed to develop matrix metalloproteinase (MMP)-sensitive peptide-modified, polyethylene glycol (PEG)-modified (PEGylated) solid lipid nanoparticles (SLNs) for loading Sch B (MMP-Sch B SLNs), and to evaluate the therapeutic effect in the myocardial infarction model. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 43 publications
(43 reference statements)
0
24
0
Order By: Relevance
“…37 Shao et al investigated the therapeutic effect of Schisandrin B (Sch B) in the form of SLN in the model of the rat myocardial infarction. 38 Schisandrin B is isolated from the fruit of Schisandra chinensis and can be clinically applied in myocardial ischemia. Polyethylene glycol (PEG) and matrix metalloproteinase-targeting peptide (MMP-TP) conjugate was synthesized in the study.…”
Section: Carbon-based Nps Nanotubesmentioning
confidence: 99%
See 2 more Smart Citations
“…37 Shao et al investigated the therapeutic effect of Schisandrin B (Sch B) in the form of SLN in the model of the rat myocardial infarction. 38 Schisandrin B is isolated from the fruit of Schisandra chinensis and can be clinically applied in myocardial ischemia. Polyethylene glycol (PEG) and matrix metalloproteinase-targeting peptide (MMP-TP) conjugate was synthesized in the study.…”
Section: Carbon-based Nps Nanotubesmentioning
confidence: 99%
“…The authors demonstrated that the developed formulation is the optimal carrier of API for the myocardium tissues and effectively protects the heart against acute myocardial infarction. 38 The possibility of using porous silicon nanoparticles (PSi) in cardiovascular disease therapy was also assessed. The Finnish team attempted to develop PSi-based nanosystems for targeted therapy and diagnosis of myocardial infarction.…”
Section: Carbon-based Nps Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shao et al showed that the antioxidant and anti-inflammatory agent Schisandrin B's (Sch B's) encapsulation within a matrix-metalloproteinasesensitive peptide-modified and PEG-modified (PEGylated) solid lipid nanoparticle (MMP-Sch B SLN) leads to promising in vitro and in vivo outcomes in the context of treating MI. 41 Shao et al demonstrated that their novel formulation of MMP-Sch B SLN significantly reduced the percentage of infarct sizes relative to the Sch B solution and saline control (19.2, 36.5, and 43.2%, respectively) in rat MI models. 41 Furthermore, through their pharmacokinetic and biodistribution experiments, the authors have further demonstrated that the encapsulation of Sch B into their lipid-based carrier yields improved therapeutic characteristics, such as a prolonged plasma circulation time of encapsulated Sch B (up to more than 48 hours) when compared with Sch B solution (cleared from circulation within 4 hours).…”
Section: Nanotechnology and Its Applications In Treating Mi-associatementioning
confidence: 99%
“…41 Shao et al demonstrated that their novel formulation of MMP-Sch B SLN significantly reduced the percentage of infarct sizes relative to the Sch B solution and saline control (19.2, 36.5, and 43.2%, respectively) in rat MI models. 41 Furthermore, through their pharmacokinetic and biodistribution experiments, the authors have further demonstrated that the encapsulation of Sch B into their lipid-based carrier yields improved therapeutic characteristics, such as a prolonged plasma circulation time of encapsulated Sch B (up to more than 48 hours) when compared with Sch B solution (cleared from circulation within 4 hours). Additionally, Zhang et al demonstrated that the encapsulation of the antioxidant baicalin (BN) within non-PEGylated and PEGylated nanostructured lipid carriers (BN-NLC and BN-PEG-NLC, respectively) functioned as viable therapies for MI, with the BN-PEG-NLC showing as the most promising therapeutic characteristics.…”
Section: Nanotechnology and Its Applications In Treating Mi-associatementioning
confidence: 99%